2016
DOI: 10.5194/acp-16-10333-2016
|View full text |Cite
|
Sign up to set email alerts
|

One-year simulation of ozone and particulate matter in China using WRF/CMAQ modeling system

Abstract: Abstract. China has been experiencing severe air pollution in recent decades. Although an ambient air quality monitoring network for criteria pollutants has been constructed in over 100 cities since 2013 in China, the temporal and spatial characteristics of some important pollutants, such as particulate matter (PM) components, remain unknown, limiting further studies investigating potential air pollution control strategies to improve air quality and associating human health outcomes with air pollution exposure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
144
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 298 publications
(173 citation statements)
references
References 55 publications
29
144
0
Order By: Relevance
“…The CMAQ performance of chemical predictions in this study was comparable to or even better than those of other air quality studies over east Asia (Wang et al, 2009(Wang et al, , 2012Liu et al, , 2016Zheng et al, 2015;Hu et al, 2016;Zhang et al, 2016a). This study predicted relatively well for Figure 7.…”
Section: Evaluation Protocolsmentioning
confidence: 48%
See 2 more Smart Citations
“…The CMAQ performance of chemical predictions in this study was comparable to or even better than those of other air quality studies over east Asia (Wang et al, 2009(Wang et al, , 2012Liu et al, , 2016Zheng et al, 2015;Hu et al, 2016;Zhang et al, 2016a). This study predicted relatively well for Figure 7.…”
Section: Evaluation Protocolsmentioning
confidence: 48%
“…Compared with other regional modeling studies, WRF-CMAQ v5.0.2 used in this study outperformed MM5/CMAQ v4.6, which tended to underpredict the surface concentrations of major species with NMBs generally greater than −40 % and overpredict surface O 3 concentrations in most months with NMBs generally higher than 20 % over east Asia according to the evaluation results of Zhang et al (2016a). A relatively good performance of CMAQ v5.0.1 was also reported by Hu et al (2016). Global models such as GEOS-Chem and CESM tend to underpredict PM 2.5 concentrations (by about 50 % as reported by Jiang et al, 2013) and overpredict O 3 concentrations (by about 50 % as reported by in China/east Asia because of relatively coarse grid resolution and limitations in some model treatments (e.g., missing emissions of unspeciated primary PM 2.5 and discrepancies in surface layer height and vertical mixing).…”
Section: Evaluation Protocolsmentioning
confidence: 48%
See 1 more Smart Citation
“…1). The model has been updated to better predict air pollutants in China and details can be found in Hu et al (2016). The meteorological inputs were generated using WRF v3.7.1 with initial and boundary conditions from the National Center for Environmental Prediction (NCEP) FNL Operational Model Global Tropospheric Analyses dataset (Zhang et al, 2012a;NCEP, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…The uncertainties in China's emission inventory were estimated to be −14-13, −13-37, −17-54, −25-136, and −40-121 % for SO 2 , NO x , PM 2.5 , black carbon (BC), and organic carbon (OC), respectively (Zhao et al, 2011). Although the quantitative uncertainties are not provided by the MEIC inventory, it has been widely used in chemical transport models and validated against surface and satellite observations (e.g., Chen et al, 2015;Geng et al, 2015;Zheng et al, 2015;Hu et al, 2016).…”
Section: Uncertainties and Limitationsmentioning
confidence: 99%